Characteristics ofNesting Areaof Asiatic Softshell Turtle (Amyda cartilaginea) in The Indragiri River bank, Lubuk Terentang Village Gunung Toar District, Riau - Septia, Ranti; Sumiarsih, Eni; Adriman, Adriman (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
Abstract Asian softshell turtle ( Amyda cartilaginea) used to nest in the Indragiri River bank, especially in the Lubuk Terentangvillage. Characteristics of nesting area preferred by the softshell turtles, however are almost unknown. A research aimed to understand the nesting area characteristic ofthe turtlewas conducted from May- June 2018, coincidence with the nesting time of the turtles. Parameters studied were the slope of theriver bank, distance between the nest andwater edge, sand texture, types of vegetation around the nest, number of nest present and water quality of the IndragiriRiver. Results shown that the softshell turtle nestswere found only in the Eastern part of the Lubuk Terentangvillage. The River bank slopein the nesting area ranged from 1.56–1.72%, distance between water edge and the nest ranged from 29 – 31.5 m, substrate texture was dominated by sand (>91%), the number of nest present in Eastern was 3 nest,the nest temperature was 29–38 0C and nest humidity was 45–75 %. Water quality of the Indragiri River are as follows: temperature was29-330C, current speedwas0.14- 0.35 m/s, turbidity was 12.99- 20.75 FTUand pH was 6. In this research turtle nests were found in sandy areas with few vegetation. Keywords :river bank slope, reptil, river bank, softshell turtle nest